Gambaran Pelaksanaan Supervisi Kepala Ruang Terhadap Perawat Pelaksana Dalam Keselamatan Pasien - Maria Hariyati Oktaviani; Muhamad Rofii (Persatuan Perawat Nasional Indonesia Jawa Tengah, 2019)
The implementation of supervising the head of a room in one hospital in Semarang has not been optimal due to the absence of a schedule, assessment instruments, guidance, documentation of supervision results, and standard operating procedures (SOP) supervision. Supervision activities are incidental in accordance with needs and have not been implemented in a structured and well-documented manner. The writing of this article aims to find out the description of the implementation of head supervision in a hospital in Semarang. This study uses descriptive research design. The subjects in this study were all heads of inpatient rooms. The object of this research is the implementation of the supervision of the head of the room according to the SOP and the results of documentation of the implementation of supervision. The instrument in this study used a draft sheet for evaluation of the superficial room leader evaluation. Shows that there is a change in the implementation of supervision based on the SOP before and after the dissemination of supervision is carried out to the head of the room. Documented supervision results can help the head of the room to see the extent of the ability of staff and can jointly improve capabilities, correct errors in improving the quality of nursing care services. The implementation of supervising the head of a room in one of the Semarang hospitals needs to be improved, especially in terms of post-supervision documentation, development of thematic supervision themes, and structured supervision scheduling.